2018
DOI: 10.1002/celc.201800830
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Growth of a Feather‐like MnO2 Nanostructure on Carbon Paper for High‐Performance Rechargeable Sodium‐Ion Batteries

Abstract: Recently, sodium‐ion batteries have attracted great attention, owing to the rich resource and low cost. In the present work, a feather‐like MnO2 nanostructure was prepared directly on carbon paper by using a rapid and simple hydrothermal route for the first time. The formation mechanism was proposed by investigating the intermediate products during the reaction. When applied as an anode for a sodium‐ion battery, the feather‐like MnO2 nanostructure on carbon paper exhibited a high discharge capacity, good rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…This MnO@C hybrid exhibited a reversible capacity of 260 mAh g −1 after 100 cycles at a specific current of 50 mA g −1 . [99] Li et al [100] reported feather-like MnO 2 grown on carbon paper by a hydrothermal method and applied this composite as negative active material for SIBs, providing a rather high reversible capacity of 300 mAh g −1 after 400 cycles at 0.1 A g −1 . Peng and coworkers [101] synthesized ultrafine MnO nanoparticles, with a particle size of 4 nm, anchored on nitrogen-doped CNTs (NDCT@MnO) as anode active material for SIBs.…”
Section: Manganese Oxide (Mno Mn 3 O 4 Mno 2 )mentioning
confidence: 99%
“…This MnO@C hybrid exhibited a reversible capacity of 260 mAh g −1 after 100 cycles at a specific current of 50 mA g −1 . [99] Li et al [100] reported feather-like MnO 2 grown on carbon paper by a hydrothermal method and applied this composite as negative active material for SIBs, providing a rather high reversible capacity of 300 mAh g −1 after 400 cycles at 0.1 A g −1 . Peng and coworkers [101] synthesized ultrafine MnO nanoparticles, with a particle size of 4 nm, anchored on nitrogen-doped CNTs (NDCT@MnO) as anode active material for SIBs.…”
Section: Manganese Oxide (Mno Mn 3 O 4 Mno 2 )mentioning
confidence: 99%
“…In these structures, the basic structural unit MnO 6 octahedra is connected to each other by co‐angle/co‐edge, constructing chain, tunnel, layered structures with enough space accommodating foreign cations . Given this structural advantage, MnO 2 has been extensively investigated as favorable cathodes for batteries in the past several years, including Li‐ion batteries, Na‐ion batteries, K‐ion batteries, Mg‐ion batteries, and latest ZIB . Theoretically, MnO 2 can accommodate one Zn 2+ insertion per formula with a high theoretical capacity of approximately 616 mAh/g, in which the Mn 4+ is reduced to Mn 2+ .…”
Section: Manganese‐based Oxidesmentioning
confidence: 99%
“…The present capacity of the Ni(5)-Mn 3 O 4 (1) @CMK-5 electrode in SIBs is greater or analogous to other manganese oxide-supported electrodes publicized previously. 18,27,[65][66][67] The comparison of capacity of the current electrode with other publicized manganese oxide based electrode materials for SIBs was made in Table S3 (SI). The excellent capacity of the Ni(5)-Mn 3 O 4 (1) @CMK-5 anode in SIBs can also be attributed to enhanced electronic conductivity of Mn 3 O 4 NPs due to Ni doping and smaller NP size that helps in solid state Na + ion diffusion.…”
Section: Electrochemical Performances Of Nanocomposite In Sibsmentioning
confidence: 99%